Film copyright in the European Union - Kamina, Pascal (Cambridge studies in intellectual property rights., 2002)
In the first book on this subject, Kamina analyses film protection in the fifteen member states of the EU, with emphasis on Britain and France. He addresses key aspects of film copyright, including the protection of film works within the EU in the context of European harmonization of copyright laws.